1997
DOI: 10.1002/(sici)1096-8644(199702)102:2<203::aid-ajpa5>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

In vivo bone strain patterns in the zygomatic arch of macaques and the significance of these patterns for functional interpretations of craniofacial form

Abstract: It has been proposed that the mammalian facial skeleton is optimized for countering or dissipating masticatory stress. As optimized load-bearing structures by definition exhibit maximum strength with a minimum amount of material, this hypothesis predicts that during chewing and biting there should be relatively high and near uniform amounts of strain throughout the facial skeleton. If levels of strain in certain areas of the facial skeleton are relatively low during these behaviors, this indicates that the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
186
1
4

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 181 publications
(211 citation statements)
references
References 50 publications
20
186
1
4
Order By: Relevance
“…For instance, among Plio-Pleistocene hominins, Paranthropus is distinguished by a heavily developed masticatory complex widely considered as adapted for producing and countering increased masticatory stresses associated with hard and/or tough food items (Tobias, 1967;du Brul, 1977;Walker, 1981;Rak, 1983;Demes and Creel, 1988;Hylander, 1988;Daegling, 1989;Constantino and Wood, 2007). Current understanding of the primate face from experimental data supports assertions that this region is under strong selective pressures related to masticatory activity (Hylander, 1979a(Hylander, ,b,c, 1988(Hylander, , 1992Hylander and Johnson, 1997;Ravosa et al, , 2007aRavosa et al, ,b, 2008a. The hard palate of Paranthropus, which is relatively ''deep'' or superoinferiorly tall, further characterizes the genus when compared with its sister taxon Australopithecus (Ward and Kimbel, 1983;McCollum et al, 1993).…”
mentioning
confidence: 89%
“…For instance, among Plio-Pleistocene hominins, Paranthropus is distinguished by a heavily developed masticatory complex widely considered as adapted for producing and countering increased masticatory stresses associated with hard and/or tough food items (Tobias, 1967;du Brul, 1977;Walker, 1981;Rak, 1983;Demes and Creel, 1988;Hylander, 1988;Daegling, 1989;Constantino and Wood, 2007). Current understanding of the primate face from experimental data supports assertions that this region is under strong selective pressures related to masticatory activity (Hylander, 1979a(Hylander, ,b,c, 1988(Hylander, , 1992Hylander and Johnson, 1997;Ravosa et al, , 2007aRavosa et al, ,b, 2008a. The hard palate of Paranthropus, which is relatively ''deep'' or superoinferiorly tall, further characterizes the genus when compared with its sister taxon Australopithecus (Ward and Kimbel, 1983;McCollum et al, 1993).…”
mentioning
confidence: 89%
“…In a later paper, Hylander and Johnson (1997) reported that strain magnitudes also vary within the zygomatic arch, being higher anteriorly than posteriorly. They argued that if optimality is defined as maximum strength with minimum material, the extreme variability in bone strain magnitudes across the facial skeleton falsifies the general assumption that the facial skeleton is optimized for resisting forces generated during routine mastication.…”
Section: Introductionmentioning
confidence: 95%
“…For example, the model and experimental data differ in some ways that affect attempts at validation. Published experimental data typically consist of peak strain values for a number of anatomical regions (Hylander and Johnson, 1997), although these regions may not experience peak strain simultaneously (Hylander and Johnson, 1994;Ross, 2001). However, strains occur simultaneously in static FE models.…”
Section: Validation and Interpretationmentioning
confidence: 99%
“…We selected Macaca fascicularis because of the in vivo strain data available for this taxon (Hylander et al, 1991a;Hylander and Johnson, 1997). We obtained CT scans of the skull and manually digitized the scans in Solidworks CAD modeling software to create a virtual solid model including external and internal surfaces (Fig.…”
Section: Geometry and Meshmentioning
confidence: 99%
See 1 more Smart Citation